The Proceedings from Halophiles 2013, the International Congress on Halophilic Microorganisms - Antonio Ventosa (Frontiers Research Topics, 2015)
The Halophiles 2013 meeting is a multidisciplinary international congress, with a strong history of regular triennial meetings since 1978. Our mission is to bring researchers from a wide diversity of investigation interests (e.g., protein and species evolution; niche adaptation, ecology, taxonomy, genomics, metagenomics, horizontal gene transfer, gene regulation; DNA replication, repair and recombination; signal transduction; community assembly and species distribution; astrobiology; biotechnological applications; adaptation to radiation, desiccation, osmotic stress) into a single forum for the integration and synthesis of ideas and data from all three domains of life, and their viruses, yet from a single environment; salt concentrations greater than seawater. This cross-section of research informs our understanding of the microbiological world in many ways. The halophilic environment is extreme, especially above 10% NaCl, restricting life solely to microbes. The microorganisms that live there are adapted to extreme conditions, and are notable for their ability to survive high doses of radiation and desiccation. Therefore, the hypersaline environment is a model system (both the abiotic, and biologic factors) for insightful understanding regarding conditions and life in the absence of plant and animals (e.g., life on the early earth, and other solar system bodies like Mars and Europa). Lower salinity conditions (e.g., 6-10% NaCl) form luxuriant microbial mats considered modern analogues of fossilized stromatolites, which are enormous microbially produced structures fashioned during the Precambrian (and still seen today in places like Shark's Bay, Australia). Hypersaline systems are island-like habitats spread patchily across the earth's surface, and similar to the Galapagos Islands represent unique systems excellent for studying the evolutionary pressures that shape microbial community assembly, adaptation, and speciation. The unique adaptations to this extreme environment produce valuable proteins, enzymes and other molecules capable of remediating harsh human instigated environments, and are useful for the production of biofuels, vitamins, and retinal implants, for example. This research topic is intended to capture the breadth and depth of these topics.